Eleusine Indica for Food and Medicine - Zikry Hamizan, Md Zakri; Monica, Suleiman; Shean, Yeaw Ng; Zainab, Ngaini; Salahaudin, Maili; Fatimah, Salim (UNISZA, 2021)
Eleusine indica, a perennial herb that belongs to the Poaceae family, is locally known as “rumput sambau”. The species can be found in the tropical regions and it is the only species of Eleusine in Malaysia. In India, some parts of the plant such as the roots and the seeds are used as food and can be eaten raw or cooked. The young seedling is also used as a side dish with rice, while the seeds are sometimes used as a famine food. Although this grass is not considered as food in Malaysia, the local people utilise it to treat various ailments such as hastening the placenta delivery after childbirth, pain relieve for vaginal bleeding, asthma, fever, urinary infection, haemorrhoids, and tonic for flu related symptoms. Due to wide spectrum of traditional usage, a complete review of E. indica which focusing on food and medicinal perspectives is necessary to organize and evaluate its potential for further studies and commercial exploitation. The information on the species was collected from scientific journals, books, and reports searched through available databases such as Google Scholar, PubMed, Directory of Open Access Journals, Science Direct, Bioline International, and Reaxys. Contextually, the present review reveals that apart from the roots, the plant is relatively safe to ingest. It represents a rich source of nutrients and contains therapeutic phytochemicals such as flavonoids, steroids, essential oils, cardiac glycosides, coumarins, fatty acids, anthraquinones, anthrones, triterpenes, tannins, and alkaloids. Thus, E. indica can be considered as a natural reservoir for both food and medicine.